Les ressorts territoriaux de la gestion de l’eau : le cas de la Drôme (1980-2013) - Sabine Girard (VertigO)
River contracts and Plans for Water Development and Management are some of the new public action instruments issued of the water policy regionalization. The objective of this article is to explore the mechanisms and conditions through which regional water management can contribute to environmental efficiency. The efficiency is approached as a question of strategic action for water managers. Research suggests the hypothesis that this efficacy depends on how actors implementing these systems apprehend their regional dimensions. It proposes the idea of territorial feedback to indicate all the regional and regionalizing resources resulting from dialectic and diachronic processes between regional constructions concerning water and projects for its management. The demonstration uses the empirical case of the Drôme valley over the past three decades. The results of the research highlight three types of territorial feedback: arguments allowing agreements in negotiation process; tools of strategic action to change water users’ practices; sources of legitimization allowing water managers to increase their means of action. The link between the policies of water management and the policies of territorial development forms an additional territorial feedback. The role of water managers seems determining and their intentions, their power and their skills in territorial matters are discussed.